SOLIDITY AND IMMUTABILITY OF BEHAVIOURAL FINANCE THEORY IN CAPITAL MARKET INVESTMENT: A GLOBAL PERSPECTIVE - Agwu, Ejem Chukwu (American Finance & Banking Review, 2023)
This study evaluated the argument that the capital market is efficient such that all information from both the past, present, and unpublished have already been reflected in the market price of security as a guide for investors in the market and that the behavior of the same investors could affect the performance of the market. To address the above concern, the researcher employed various suitable final metric tools such as the Normality/Random Walk test, Variance ratio test, EGARCH models, etc., to analyze the daily historical data from prominent capital markets, each from all the continents around the world. From the results of these tools employed, none of the markets under study follow the random walk theory within the scope of the study. The results of EGARCH and volatility clustering tests also revealed that all the countries under study exhibited the property of stock returns distribution called volatility clustering or volatility pooling, a kind of heteroscedasticity, suggesting the nonconformity of the random walk theory. The failure of the various results to corroborate the random walk theory shows that investors are rational and unpredictable. These results have rightly positioned the behavioral finance theory as a veritable tool that can guide economic agents on capital market investment decisions. That means the behavior of investors makes share prices deviate from the economic fundamentals or assumptions. Considering the above findings, the researcher boldly advocates for a paradigm shift to behavioral finance theory, where emotions and psychology or mindsets of investors influence the investment decision-making process and financial markets, hence a veritable guide for decisions on stock market investments. Therefore, the researcher suggested that emotional and psychological checks be carried out on all stock market investors, mainly when an innovation or new policy is promulgated.JEL Classification Codes: C32, C58, G14, G41.